Odpowiedzi

2009-11-22T15:43:50+01:00
A)(x+1)(x-2)+(x+2)(x-1)=2x-2x+1x-2+2x-x+2x-2=4x-4
b)(4y+3)(y-2)-2y(4-2y)=4y²-8y+3y-6-8y+4y=4y²+7y
c)2(3a²-1)-(a+2)(a+2)=6a²-2-2a+2a+2a+4=6a²+2+2a
  • Aga9
  • Początkujący
2009-11-22T15:52:05+01:00
Zad.1. Zapisz w jak najprostszej postaci:
a.) (x+1)(x-2)+(x+2)(x-1)=x(x-2)+1(x-2)+x(x-1)+2(x-1)=x²-2x+x-2+x²-x= 2x²-2x-2
b.) (4y+3)(y-2)-2y(4-2y)=4y(y-2)+3(y-2)-8y+4y²=4y²-8+3y-6-8y+4y²= 8y²-14-5y
c.) 2(3a²-1)-(a+2)(a+2)=6a²-2-a(a+2)+2(a+2)=6a²-2-a²-2a+2a+4= 6a²-2-a²-2a+2a+4=5a²+2